THE EFFECT OF MULTIPLE ROLES AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE, WITH MOTIVATION AS A MODERATING VARIABLE AT THE POPULATION CONTROL AND FAMILY PLANNING OFFICE OF CENTRAL SULAWESI PROVINCE. - Grace, Meity; Kornelius, Yoberth; Mahardiana, Lina (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2025)
This study investigates the impact of multiple roles on employee performance; the effect of work discipline on employee performance; the influence of various roles on employee performance with motivation as a moderating variable; and the impact of work discipline on employee performance with motivation as a moderating variable. The research applies a quantitative method and utilizes SEM-PLS for hypothesis testing. Purposive sampling was used based on specific criteria, yielding a sample of 42 individuals. The results showed that multiple roles negatively and significantly affected employee performance (p < 0.05). Work discipline significantly and positively influenced employee performance (p < 0.05; p = 0.021). Motivation, as a moderating variable, enhanced the effects of multiple roles and work discipline on employee performance (p < 0.05)